The practice of medicinal chemistry - Wermuth, C. G.; Aldous, David (David John); Raboisson, Pierre; Rognan, Didier (London, UK : Academic Press, 2015)
The Practice of Medicinal Chemistry, Fourth Edition, provides a practical and comprehensive overview of the daily issues facing pharmaceutical researchers and chemists. In addition to its thorough and excellent treatment of basic medicinal chemistry principles, this updated edition has been thoroughly revised to provide new and expanded coverage of the latest technologies and approaches in drug discovery. With in-depth coverage of high content screening, scoring, docking, binding free energy calculations, polypharmacology, QSAR, chemical collections and databases, and much more, this book is the go-to reference for all academic and pharmaceutical researchers who need a complete understanding of medicinal chemistry and its application to drug discovery and development.
VI. Methods for Target Identification and ValidationA Affinity Chromatography; B Genetic Methods; C Haploinsufficiency Profiling in Yeast; D Analysis of Resistant Mutants; E siRNA for Target Validation; F Yeast Three-Hybrid System; G DNA Microarrays; H Comparative Profiling; I Analysis of the Pathophysiology; J The Study of Existing Drugs; K Systems Biology; L In Silico Simulation of the Human Patient; VII. Target Validation; VIII. Conclusion; References; II. Lead Compound Discovery Strategies; 4 Strategies in the Search for New Lead Compounds or Original Working Hypotheses; I. Introduction.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed July 9, 2015).
Includes bibliographical references and index.
Print version record.
Keywords: Pharmaceutical chemistry; Drugs -- Design; Drugs -- Design; Pharmaceutical chemistry; MEDICAL / Pharmacology; Electronic books; Electronic books